DEVELOPMENT AND INNOVATION OF SENDANG BATIK DESIGN AND MOTIVATION DURING THE NEW NORMAL TIME WITH SIWALAN LEAF AND FRUIT MOTIF - Ruswaji Ruswaji; Moh. Muklis Sulaeman; Bimbie Febrian A. (UNIVERSITAS PAKUAN, 2021)
Batik art is a local cultural heritage that stores knowledge and local wisdom of high value. In other words batik is a craft that has high artistic value and has long been a part of Indonesian culture. Therefore Sendang Lamongan batik is one of the cultural heritage that needs to be preserved, protected and supported by its development. This devotion tries to develop the design of Batik Sendang Lamongan motif as a result of cultural acculturation of its people, so that it can be an asset for cultural heritage. The focus and priority of design development motifs depart from the problem is still limited variety of existing ornaments. The purpose of this program is to improve the quality of batik products through the development of batik motif designs based on local wisdom. Second, expanding the market segment, not only in lamongan area but also other regions including outside east Java province. This program method is a discussion and observation conducted to identify problems, conduct activities, training workshops on the development of batik motifs based on local wisdom, followed by mentoring, monitoring and evaluation. This program produces new batik motifs based on local wisdom from flora natural sources, namely with The Leaves and Fruits of Borassus.